AN ANALYSIS OF IDIOMATIC MEANING EXPRESSION FOUND ON VLOG VIDEO BY CINTA LAURA - Budik Kusworo (IAI Al-Qolam, 2022)
The aims of this study are (1) to find out the types of idiomatic expressions used in Cinta Laura's vlog. (2) To describe the meaning of the idioms used in the vlog by Cinta Laura. In analyzing the data, this study uses content analysis techniques by comparing the data, and verbally describing, then interpreting the findings to make conclusions. Moreover, the research found 24 idiomatic expressions from5 content youtube vlog vidio Cinta Laura. Where each vlog vidio content has a different duration. Then from the 24 idiomatic expressions, 11 idioms were found that belong to the idiomatic type use by Cinta Laura based on the theory of FacitilyO’dell and McCarthy. There are 6 types of idiomatic expressions based on theory Facility O’dell and McCarthy, of wich only 4 conveyed by Cinta Laura in someof her vidio vlog. and of the 4 types found by the researcher, the one that is often used in idiomatic expressions in the vlog vidio is the type of idiomin the formof a fixed statements found in the idiomatic expressions and the second is in the formof proverb of idiomatic expressions which are include in the proverb types, thereare 2 types, while the third, namely the idiomatic types in the formof cliches asmany as 2 idiomatic expressions, and the last type of idiomatic in the formof binomials, namely only there is one idiomatic expression that belongs to this type. Keywords: Linguistics, Idiomatic, Vlog Video,